FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Handayani, Dwi (Widya Warta, 2009)
The  quality of auditing is the main focus of auditor ’s work in order to discover and report any breach in the accounting system of client’s company. It is determined by both competency and independency. The determinants of auditing quality in public sector are (1) the length of time which an auditor has spent to audit client’s company, (2) the number of client’s company audited by an auditor, (3) the size and financial condition of client’s company audited, (4) auditor’s work reviewed by the third party, (5) auditor’s independency, (6) the level of auditing fee, and (7) the planning of auditing quality. The characteristics of auditing quality improvement include (1) the level of education, (2) professionalism, (3) the understanding on internal controlling structure of client’s company, (4) the planning of auditing team, and (5) auditing performance of VFM.